Comorbid Fluency Difficulties in Reading and Math: Longitudinal Stability Across Early Grades. (April 2018) - Koponen, Tuire; Aro, Mikko; Poikkeus, Anna-Maija; Niemi, Pekka; Lerkkanen, Marja-Kristiina; Ahonen, Timo; Nurmi, Jari-Erik
We examined the prevalence of comorbidity of dysfluent reading and math skills longitudinally in a representative sample ( N = 1, 928) and the stability of comorbid and single difficulties from first to fourth grades. The findings indicated that half the children who showed very low performance in one skill also evidenced low or very low performance in the other. Comorbid difficulties had somewhat higher prevalence in third and fourth graders than in first and second graders. The stability of comorbid difficulties was found to be established from Grade 2 onward, but the stability of single difficulties increased steadily across grades. Overall, the findings emphasize the relatively strong stability of comorbid difficulties after the second grade and underscore the need for close monitoring of, and support for, both skills as opposed to just one.